Roland Barthes' Semiotic Analysis of Meme Content on the @Tokopedia Account on Tiktok - Lestari, Martha Tri; Agustian, Muhamad Sabiq (Jurnal Ilmiah Komunikasi Makna, 2025)
This study aims to analyze meme content on Tokopedia's TikTok account using Roland Barthes' semiotics approach. The background of this research is the use of social media by e-commerce companies to interact with consumers creatively and efficiently. The research problem is how meme content on Tokopedia's TikTok account conveys communication messages. This study employs a descriptive qualitative method focusing on a detailed and systematic depiction of phenomena. The analysis covers two levels of meaning in meme content: denotation and connotation, as well as a third system of signs, myth. The theoretical foundation used is Roland Barthes' semiotics, which explores literal meanings, deeper associations, and myths formed from these signs. The results show that Tokopedia uses visual and narrative symbols to strengthen its brand identity and convey messages related to efficiency and modernity. The myths created from Tokopedia's meme content reflect the brand as part of a dynamic and modern lifestyle, offering smart and enjoyable shopping solutions. The conclusion of this study highlights the importance of semiotic analysis in understanding how signs and symbols can be effectively used in digital marketing communication to build strong narratives and influence audience perceptions.